Review Interaksi Obat-Obat Potensial Terapi Antibiotik Pada Infeksi Saluran Pernafasan Pasien Anak Rawat Inap Di Rumah Sakit - Ainaya Rizqiah; Amitasari Damayanti (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Drug interaction is a pharmacological or clinical response to the administration of drugs in combination or concurrently that can change the effectiveness of one drug with another drug. These effects can be dangerous if drug interactions lead to increased toxicity or decreased therapeutic effectiveness of a drug. Antibiotics are a treatment used for pediatric with respiratory infections. Overuse of antibiotics can lead to antimicrobial resistance. The purpose of the literature review study was to determine the types of antibiotic drug interactions and analyze the severity of antibiotic drug interactions in pediatric patients with respiratory tract infections who were hospitalized and carried out using the narrative review method. The results showed that there were interactions between antibiotics with antibiotics and antibiotics with other drugs with moderate and major severity, and there were types of pharmacokinetic and pharmacodynamic drug interactions in pediatric patients with respiratory tract infections.